2016
DOI: 10.1007/s00438-016-1238-4
|View full text |Cite
|
Sign up to set email alerts
|

The starch-bound alpha-amylase/trypsin-inhibitors in Avena

Abstract: Oat kernels exhibit an extra-soft texture, a trait recently demonstrated to be largely modulated by starch-bound tryptophan-rich 2S proteins, the vromindolines. In this study, fractionation by two-dimensional electrophoresis of starch-bound proteins in 25 oat (Avena sativa) cultivars and 11 diploid or tetraploid Avena species revealed novel 2S proteins called Avena α-amylase/trypsin-inhibitors (AATI) because of their sequence similarity with wheat α-amylase/trypsin inhibitors. Thirty-seven AATI polypeptides, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 34 publications
1
11
1
Order By: Relevance
“…The inhibitions of α-glucosidase and α-amylase delay glucose absorption and reduce postprandial blood glucose levels [ 23 ]. In this study, the α-glucosidase inhibitory activities of 235 strains were investigated to identify strains with potential hypoglycemic activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibitions of α-glucosidase and α-amylase delay glucose absorption and reduce postprandial blood glucose levels [ 23 ]. In this study, the α-glucosidase inhibitory activities of 235 strains were investigated to identify strains with potential hypoglycemic activity.…”
Section: Resultsmentioning
confidence: 99%
“…The therapeutic strategies for T2DM include stimulating insulin secretion, increasing the activity of insulin in the target tissues, oral hypoglycemic agents, and inhibition of α-glucosidase [ 27 ]. Numerous studies have demonstrated that the α-glucosidase inhibitory and α-amylase inhibitory activities of probiotics may be beneficial for glycemic regulation [ 28 , 29 ]. Probiotics have been reported to alleviate T2DM by regulating glucose metabolism and improving insulin sensitivity through several mechanisms, including the production of metabolites, such as SCFAs [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rye grain contains dimeric inhibitors highly homologous to the wheat dimeric 0.19 and 0.53 inhibitors (79,80) and a trypsin inhibitor ( 81), but no tetrameric forms have been reported. Seventeen ATI-like proteins which exhibit up to 60% similarity with wheat CM proteins have been reported in oats (82). ATI-enriched extracts from barley and rye showed TLR4 activation comparable to wheat, which was not detected in extracts from oats and other non-gluten containing cereals (50).…”
Section: Atis In Other Types Of Wheat and Related Cerealsmentioning
confidence: 99%
“…Oat alpha-amylase/trypsin inhibitors 1, 2, and 3 (of approximately 30% identity) have different primary structures, molecular weights and, isoelectric points (pI). These inhibitors exhibit the highest sequence similarity with the components of the wheat tetrameric amylase/trypsin inhibitors, which are referred to as CM (chloroform/ethanol mixture solubility) proteins [61,62,63]. Each wheat amylase/trypsin inhibitors, about 60 kDa in size, contains one copy of either the CM1 or CM2 protein, one copy of either the CM16 or CM17 protein, and two copies of the CM3 protein.…”
Section: The Possible Similarity Between Oat and Wheat Amylase/trymentioning
confidence: 99%
“…The amount of the alpha-amylase/trypsin inhibitors is different during the development of caryopses in the vegetative period. The maximum inhibitor amount in the starch granules of caryopses is reached 35 days after anthesis [61,62].…”
Section: The Possible Similarity Between Oat and Wheat Amylase/trymentioning
confidence: 99%